1998
DOI: 10.1097/00006842-199805000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity in Patients With Burning Mouth Syndrome

Abstract: BMS has high psychiatric comorbidity but can occur in the absence of psychiatric diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
3
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 40 publications
6
88
3
5
Order By: Relevance
“…In any case, different studies have confirmed that BMS patients have a high prevalence of psychological problems such as anxiety, depression, irritability, and an increased desire to isolate themselves, compared with the control subjects (4,5). On the other hand, although psychological factors are present in a large proportion of all cases of BMS, a substantial percentage on individuals develop the syndrome without any psychological disorders (6). This indicates that psychological disorders are not the only or exclusive cause underlying BMS.…”
Section: Resultsmentioning
confidence: 98%
“…In any case, different studies have confirmed that BMS patients have a high prevalence of psychological problems such as anxiety, depression, irritability, and an increased desire to isolate themselves, compared with the control subjects (4,5). On the other hand, although psychological factors are present in a large proportion of all cases of BMS, a substantial percentage on individuals develop the syndrome without any psychological disorders (6). This indicates that psychological disorders are not the only or exclusive cause underlying BMS.…”
Section: Resultsmentioning
confidence: 98%
“…In this context, it has been proposed that psychiatric disorders could explain the occurrence of BMS [15,16,17,18,19,20]. Several studies have reported elevated psychiatric morbidity in BMS, mainly depression, anxiety and hypochondriasis [15,16,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported elevated psychiatric morbidity in BMS, mainly depression, anxiety and hypochondriasis [15,16,17,21]. Depression is the most prevalent psychiatric disorder in patients with BMS [15,16,17,20]. Furthermore, personality traits such as neuroticism, extraversion, openness and conscientiousness seem to differentiate BMS patients from controls [17].…”
Section: Introductionmentioning
confidence: 99%
“…It often occurs more frequently in women over 60 years in the peri-or postmenopausal period; it is rarely found in men (1,2). The etiology is unknown but it's believed to be multifactorial; patients with BMS often have anxiety and clinical depression (4,5). Among the important local factors dental trauma, the presence of tartar, rough surfaces prosthesis, allergic reactions to dental materials, chemical irritants of lipsticks, toothpastes and prolonged use of mouthwashes may be included.…”
Section: Introductionmentioning
confidence: 99%